The edge / 2. - Smith, Roland, 1951- (Peak Marcello adventure, 2015)
Fifteen-year-old Peak Marcello is invited to participate in an "International Peace Ascent" in the Hindu Kush, with a team made up of under-eighteen-year-old climbers from around the world--but from the first something seems wrong, so when the group is attacked, and most of the climbers are either killed or kidnapped, Peak finds himself caught up in a struggle to survive, shadowed by the Shen, a mysterious snow leopard.